Linfluence De Lextention De La Marque Sur Lattitude Du Consommateur (Global Journal of Management and Business Research, 2020)
This research is fitting into the field of the analysis of the consequences of brand extension on the attitude of the consumer. The study was conducted with a sample of 235 individuals, and we came out with the result that, there is a direct and positive impact of the width of a mark, as well as the similarity between extensions on the consumer's attitude, and the consumer's familiarity with the brand, has no effect on his attitude. While highlighting the interest for managers to consider, the concept of extension in the management of their brands.
Keywords: brand extension; consumer attitude; rating; brand; preference